1982
DOI: 10.1093/carcin/3.3.293
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic nitrite formation from N-nitrosamines: evidence for a cytochrome P-450 dependent reaction

Abstract: Nitrite was formed on incubation of N-nitrosamines with a reconstituted monooxygenase system, consisting of cytochrome P-450 (P-450) and NADPH P-450 reductase from pig liver. Nitrite was not obtained when the nitrosamines were incubated with NADPH P-450 reductase alone or when molecular oxygen or NADPH were omitted. Interaction of nitrosamines with the reconstituted P-450 system or with hemoglobin under reducing conditions resulted in optical spectra identical with those obtained with nitrite. It is proposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…23,55,56 Indeed, a specific increase in denitrosation of DEN to overcome deethylation as we have found in current study provides the most important mechanism for Bicyclol of preventing DNA damages, that is presumed due to the specific induction of CYP isoforms in hepatic microsome.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…23,55,56 Indeed, a specific increase in denitrosation of DEN to overcome deethylation as we have found in current study provides the most important mechanism for Bicyclol of preventing DNA damages, that is presumed due to the specific induction of CYP isoforms in hepatic microsome.…”
Section: Discussionsupporting
confidence: 58%
“…Meanwhile, metabolism of dialkylnitrosamines via hepatic microsomal P450 provide molecular targets for preventing or reducing carcinogen-induced DNA damages, the initiation of hepatocarcinogenesis. [23][24][25][26][27] Bicyclol was noted previously to induce specific CYP isoforms in rat hepatic microsomes and, therefore, reduce hepatotoxicity of aflatoxin B 1 (AFB 1 ), a potent hepatotoxin and hepatocarcinogen via the acceleration of AFB 1 metabolism. 28 In the present work, Bicyclol in alterations of hepatic mcirosomal P450 in DEN metabolisms and its protection in DEN-induced hyperplastic lesions and correlated mechanism have been studied.…”
mentioning
confidence: 99%
“…It is possible that during STZ metabolization, the liver may also take part. It has been demonstrated that the enzymatic metabolization of N-nitrosoureas, N-nitrosoguanidines and nitrosoamines in the liver results in partial denitrosylation by cytochrome P 450 reductase [46] and/or glutathione S-transferase [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…MAO participation in subsequent steps in the metabolism of N-nitrosodialkylamines is a reasonable possibility on the basis of data published thus far (4)(5)(6). It has been proposed (15,16) that N-nitrosamines are degraded to nitrite and to their respective secondary amines by hepatic cytochrome P-450. The dialkylamine thus formed could then be further metabolized to carcinogenic species by MAO catalysis, since MAO is known to catalyze the oxidation of secondary amines.…”
Section: Resultsmentioning
confidence: 99%